Comparative analysis of antibody-mediated loss-of-function versus gene knock-out and knock-down - Buck-Wiese, Marie; Liechocki, Sally; Erfle, Holger; Starkuviene-Erfle, Vytaute (SLAS discovery, 2025)
In this study we compare three methods for manipulating cell function: RNA interference (RNAi), CRISPR-Cas9 gene knock-out, and antibody-mediated loss-of-function. We have focused on analyzing changes in cell-matrix adhesion via targeting two key regulators, Talin1 (TLN1) and Kindlin-2 (KD2). Adhesion-relevant phenotypic assays revealed distinct temporal onset dynamics for each method. RNAi and CRISPR-Cas9 effectively reduced target mRNA and protein levels. In contrast, antibody transfection induced phenotypic changes without altering target expression, suggesting direct intracellular antibody-target interaction. Transcriptome analysis demonstrated that antibody transfection and CRISPR-Cas9 induced fewer deregulated mRNAs than RNAi. Furthermore, transfected antibodies and sgRNAs shared 30 % and 70 % of deregulated transcripts to their negative controls, respectively. Whereas only 10 % of overlap was recorded between targeting and control siRNAs. Our findings emphasize the importance of considering method-specific temporal dynamics of on-target phenotype appearance and off-target manifestation. Additionally, they highlight intracellular delivered antibodies as a valuable alternative for validating and complementing genetic approaches.
Online veröffentlicht: Dezember 2025
Gesehen am 03.02.2026